Constructional Approaches to English Grammar. - Trousdale, Graeme (Topics in English Linguistics, v. 57., 2008)
This collection of articles brings together new research from both established and emerging international experts in the study of English grammar, all of whom have engaged with the notion of 'construction' in their work. The research here is concerned with both synchrony and diachrony, with the relationship between Construction Grammar and other linguistic theories, and with a number of issues in the study of grammar, such as raising and control phenomena, transitivity, relative clause structure, the syntax of gerunds, attributive and predicative uses of adjectives, modality, and grammaticaliz.